Music Creation Waringin | Tabuh Kreasi Waringin - Putu Arya Krisna Devantara; I Made Dwi Andika Putra (GHURNITA: Jurnal Seni Karawitan, 2023)
In Balinese Hinduism, the banyan tree is one of the most sacred trees because it is believed to have religious values. For the creator, visually it can be seen from the roots that hang above and also spread underground, reflecting two interrelated beliefs, namely belief in Ida Sang Hyang Widhi Wasa/God Almighty and life in the universe. Its large trunk symbolizes strength and shady leaves, as a whole, can provide shade for the world's universe. From the explanation above, the creator was very interested in the existence of the banyan tree, so he was inspired to transform the object in question into a creation of Tabuh Kreasi Pepanggulan entitled "Waringin" with the media said gamelan Gong Kebyar. The source of his inspiration comes from the history of the banyan tree which used to exist in Pura Taman which is located next to the Banjar Paketan banjar hall. Previously, in Pura Taman there was a banyan tree which was quite old, but now it was cut down for one reason or another. The stylist who made this Pepanggulan Tabuh Creation Work entitled “Waringin” wanted to continue to give a positive aura about the banyan tree that had been cut down at Taman Banjar Paketan Temple. This Tabuh Kreasi Pepanggulan was made by the creator so that it can be continuously sung or performed during piodalan at Pengaruman Temple and Taman Temple. Apart from that, this Tabuh Kreasi Pepanggulan is made so that the work does not vacuum after the Final Assignment Examination (TA).